An identity-informed narrative study of teacher attrition: why long-serving teachers leave - Yeni-Palabiyik, Pinar; Gümuşok, Fatma (Routledge Journals, Taylor & Francis Ltd, 2025)
This study approaches teacher attrition as a dynamic process that develops over time and in which teachers play an active role and enact their agencies in the light of their identity tensions and craft conscience. In this sense, this narrative inquiry explored how two long-serving teachers make sense of their experiences to quit teaching after serving for nine to 18 years. Their stories unpacked some individual and contextual elements that were interwoven within the procedure that drives the teachers towards their decision to leave the profession. Teachers' relationships with other stakeholders contributed positively to their professional identity stories, aligned with their heightened craft conscience. However, financial conditions and institutional policies were defining contextual factors that negatively influenced their decisions to quit teaching, as some identity tensions remained unrelieved and consolidated. The implications for developing policies that maintain long-serving teachers in the profession are discussed, and suggestions for teacher education are provided.
Keywords: Teacher Identity; Teacher Attrition; Narrative Inquiry; Long-Serving Teachers; Craft Conscience